Coexpression of Matrix Metalloproteinase-7 and Tissue Inhibitor of Metalloproteinase-1 as a Prognostic Biomarker in Gastric Cancer. (14th September 2020) - Zhang, Yangyu; Qin, Lili; Ma, Xiaobo; Wang, Yueqi; Wu, Yanhua; Jiang, Jing
Abstract : Background. Degradation of the extracellular matrix (ECM), an essential step in tumour invasion and metastasis, is mainly dependent on the activities of both matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). This study aimed to explore whether expression of MMP-7 and TIMP-1 alone and in combination can be used as a prognostic marker for gastric cancer (GC). Method. A total of 285 patients who had undergone tumourectomy for GC were included. Gastric tumour tissues were stained immunohistochemically to evaluate expression of MMP-7 and TIMP-1. Results. Expression of MMP-7 was associated with tumour N stage and neural invasion. Multivariate Cox regression analysis suggested that expression of MMP-7 or TIMP-1 alone cannot serve as an indicator of patient prognosis; however, coexpression of MMP-7 and TIMP-1 was found to be an independent predictive factor of overall survival in patients with GC (HR = 1.74, 95% CI: 1.08-2.80). The results of stratified analysis also showed that the predictive value of MMP-7 and TIMP-1 coexpression was stronger in patients with N3 stage disease and not receiving chemotherapy. Conclusions. In conclusion, coexpression of MMP-7 and its inhibitor TIMP-1 in gastric tumour tissues is a potential prognostic marker for GC. Greater knowledge of protein expression will lead to new paradigms and possible improvements in therapeutics.